Marine particle size distribution data obtained with an Underwater Vision Profiler 6 mounted on BGC Argo float WMO6903095 - Rainer Kiko; Lars Stemmann; Sabrina Speich; Rémi Laxenaire; Edouard Leymarie; Antoine Poiteau; Herv Claustre; Camille Catallano; Marc Picheral; Alberto Baudena (PANGAEA, 2023)
Here we provide particle size and biovolume distribution data from an Underwater Vision Profiler 6, mounted on a BGC Argo Float with the WMO number 6903095. The float was deployed in a cyclonic eddy off Cape Columbine, South Africa on the 13 April 2021 close to the eddy center at 33.07 degree South, 13.89 degree East. Parking depth was set at 300 m and profiling depth initially to 600 m and later increased to 1000 m depth to maintain the float in the eddy. Profiling frequency was every three days. It stayed within this eddy for about five months and then operated East and Southeast of South Africa until it was deliberately picked up on the 17 September 2022 at 34.43 degrees South and 10.21 degrees East.